Need Of Modelling Radionuclide Transport In Fresh Water Lake System, Subject To Indian Context - Desai, Hiral; Christian, R. A. (AIP conference proceedings, 2010)
The operations of nuclear facilities results in low level radioactive effluents, which are required to be released into the environment. The effluents from nuclear installations are treated adequately and then released in a controlled manner under strict compliance of discharge criteria. The effluents released from installations into environment undergo dilution and dispersion. However, there is possibility of concentration by the biological process in the environment. Aquatic ecosystems are very complex webs of physical, chemical and biological interactions. It is generally both costly and laborious to describe their characteristics, and to predict them is even harder. Every aquatic ecosystem is unique, and yet it is impossible to study each system in the detail necessary for case-by-case assessment of ecological threats. In this situation, quantitative mathematical models are essential to predict, to guide assessment and to direct interventions.